The Hindu World of R. K. Narayan's MR. Sampath. Issue 1 (2nd January 2018) - Rothfork, John
ABSTRACT: R. K. Narayan's novel illustrates how a man matures to abandon adolescent colonial dreams by recovering a Hindu outlook and values. The 1949 novel focuses most on views associated with asrama- dharma or developmental expectations associated with four stages of life: childhood, householder, retiree, and sanyasi (ascetic). In the comic development of Sunrise Pictures, the novel illustrates how Hinduism views life stages as comparable to dramatic roles or performances for the purpose of achieving aesthetic and spiritual insight. In the end, Srinivas and Sampath reverse roles. Sampath, a mentor in the beginning, wanders away from his family as an outcast, while Srinivas succeeds in developing satisfying positions in his family and in society.